Protection, Openness and Factor Adjustment : Evidence from the manufacturing sector in Uruguay - Casacuberta, Carlos; Gandelman, Néstor (World Bank, Washington, DC, 2012)
The authors use a panel of manufacturing firms to analyze the adjustment process in capital blue collar and white collar employment in Uruguay during a period of trade liberalization when average tariff protection fell from 43 to 14 percent. They calculate the desired factor levels arising from a counterfactual profit maximization in the absence of adjustment costs, generating a measure of factor shortages or surpluses. The average estimated output gap for 1982-95 is 2 percent. The authors' policy analysis shows that trade openness affected the adjustment functions of all three factors of production. Highly protected sectors adjust less when creating jobs (reducing labor shortages) than sectors with low protection. This may be due to fears of policy reversal in highly protected sectors. Also, highly protected sectors adjust more easily (than low protection sectors) when destroying jobs (reducing labor surpluses), especially in the case of blue collar labor. This suggests that trade protection may in fact destroy rather than create jobs within industries, as firms in highly protected sectors are more reluctant to hire and more ready to fire than firms in sectors with low protection. The results for capital are qualitatively similar but quantitatively smaller, suggesting that trade protection plays less of a role in explaining adjustment costs for capital. Interestingly, export-oriented sectors have lower adjustment costs for blue collar labor but not for white collar employment or capital, suggesting that export-led growth may be particularly successful in reducing blue collar unemployment.